ANALISIS KELAYAKAN USAHATANI PADI PADA SISTEM PERTANIAN ORGANIK DI KABUPATEN BANTUL (THE SUITABLE ANALYSIS OF RICE FARM OPERATION ON ORGANIC FARMING SYSTEM IN BANTUL REGENCY - Agus, Fransiskus Xaverius; Suyono, Suyono; Hermawan, R (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2006)
More and more people are interested in organic farming business because it keeps a big profit. Released from majority of Indonesia people , especially the bureaucrats, researchers and agriculture decision makers are still confused about organic farming, exactly it is starting to appear now and the principle agent is an economic profit. The goals of this experiment are : 1.To compare the differences between organic farmings profits and conventional system (non organic farming). 2. To know the labors productivity in organic rice farm operation 3.To know the suitability of organic rice farm operation. The experiment is done in Pandak Sub district, Bantul Regency. The determination of respondents at 30 farmers done by simple random appropriate system to farmers who plant organic rice at May - August 2005. To know the profit differences between organic rice and non organic rice are analyzed by using one sample t test. The labors productivity is measured by comparing income per labor. The suitable exertion is analyzed by profit analysis, RC ratio and rentability. Analysis result shows that there is no difference between rice farm operation with conventional system and organic farm system. The labors productivity on organic rice farm operation is 56.928, is still higher than labors income in experiments location. The suitable exertion analysis is estimated by R/C ratio and rent ability. R/c ratios value is 1,81, whereas rent abilitys value is 81 %, so can be concluded that rice farm operation is suitable to be done.